DETERMINING THE WARRANTIES OF THE JUDGE OF INDEPENDENCE TOWARDS THE LEGAL POSITIONS OF THE EUROPEAN COURT OF HUMAN RIGHTS - Горінов, Павло Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: definition of guarantees of the independence of a judge, taking into account the legal position of the European Court of Human Rights. Methods of research: general scientific and special methods - epistemological, comparative-historical, sociological and hermeneutical. Results: a scientific approach was adopted to determine the essence of the guarantees of the independence of judges. The necessity of applying a system approach to determining the guarantees of independence of a judge, which follows from the understanding of the judge’s independence and the relationship between the judiciary, the court and the judge, is substantiated. The classification of these guarantees is formed. Discussion: the problem of determining the system of guarantees of the independence of judges within the framework of constitutional and administrative law, modern issues regarding the guarantees of independence of judges in the decisions of the European Court of Human Rights. The article is devoted to the definition of guarantees of independence of judges, taking into account the legal positions of the European Court of Human Rights. The necessity of providing a system of guarantees of the independence of a judge, which includes general and special guarantees, is proved. The constitutional and legal basis for the general guarantees of the independence of a judge is the constitutional formula for guaranteeing the independence and immunity of a judge by the Constitution and laws of Ukraine, and the prohibition of any influence on a judge (ch. 1, 2 st. 126). Special guarantees of the independence of judges, based on the legal position of the ECHR, include material and procedural guarantees. The latter relates to the formation of a proper legal procedure for review and resolution of cases in the courts, the adoption of a justice decision. It is substantiated that the guarantees of independence of a judge should be indicated not in the elemental, but in the systemic meaning, that is, as a guarantee system. It is determined that the application of a system approach to determining the guarantees of independence of a judge derives from an understanding of the independence of the judge and the relationship between the judiciary, the court and the judge. It is proved that the system of guarantees of the independence of the judge constitutes general and special guarantees. The existence of general guarantees is due to the fact that the courts in Ukraine carry out exclusively courts. The existence of general guarantees is due to the fact that the courts in Ukraine carry out exclusively courts. Special guarantees of the independence of judges, based on the legal position of the ECHR, include material and procedural guarantees. Material special guarantees are related to the formation of the judiciary, the implementation of appropriate procedures.